All- and mixed-dielectric grating for Nd:glass-based high-energy pulse compression - Yuxing Han; Hongchao Cao; Fanyu Kong; Yunxia Jin; Jianda Shao (High Power Laser Science and Engineering, 2023)
Maximizing the energy-loading performance of gratings is a universal theme in high-energy pulse compression. However, sporadic grating designs strongly restrict the development of high-power laser engineering. This study proposes an all- and mixed-dielectric grating design paradigm for Nd:glass-based pulse compressors. The solution regions are classified according to the line density. High diffraction efficiency solutions are described in more detail based on the dispersion amount and incident angle. Moreover, an energy scaling factor of 7.09 times larger than that of the National Ignition Facility’s Advanced Radiographic Capability (NIF-ARC) is obtained by taking advantage of the low electric field intensity at transverse magnetic polarization and a small incident angle. These results make a pioneering contribution to facilitate future 20–50-petawatt-class ultrafast laser systems.